Development of E-Modules to Improve Higher Level Thinking Skills in Basic Accounting Subjects at Vocational Schools - Jayanti, Fitria; Suarman, Suarman; Syahza, Almasdi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
This research aims to develop learning resources in the form of electronic modules created to improve or explore students' higher order thinking abilities (HOTS) that are valid, practical and effective. The method used in this research is Research and Development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation and Evaluation. The feasibility of the E-Module which was developed based on the results of module expert validation obtained a result of 97.7% with very valid product criteria or suitable for use and based on material expert validation, a result of 94.5% was obtained with the product criteria being very valid or suitable for use. Based on the results of implementation in the field by basic accounting subject educators and students, the practicality of the E-Module developed received an assessment of the teacher's response with an average percentage score. -an average of 88.28% with very practical criteria and student responses with an average percentage score of 87.25% with very practical criteria. Furthermore, the E-Module developed was proven to be effective based on the results of the T-test and N test analysis -gain score is 0.842, which is in the high category. Based on this, the use of this E-Module is considered effective in improving students' high-level thinking abilities.